Vaccine Effectiveness Against Influenza Hospitalization Among Children in the United States, 2015–2016. (28th February 2020) - Feldstein, Leora R; Ogokeh, Constance; Rha, Brian; Weinberg, Geoffrey A; Staat, Mary A; Selvarangan, Rangaraj; Halasa, Natasha B; Englund, Janet A; Boom, Julie A; Azimi, Parvin H; Szilagyi, Peter G; McNeal, Monica; et al.
Abstract: Background: Annual United States (US) estimates of influenza vaccine effectiveness (VE) in children typically measure protection against outpatient medically attended influenza illness, with limited data evaluating VE against influenza hospitalizations. We estimated VE for preventing laboratory-confirmed influenza hospitalization among US children. Methods: We included children aged 6 months–17 years with acute respiratory illness enrolled in the New Vaccine Surveillance Network during the 2015–2016 influenza season. Documented influenza vaccination status was obtained from state immunization information systems, the electronic medical record, and/or provider records. Midturbinate nasal and throat swabs were tested for influenza using molecular assays. We estimated VE as 100% × (1 – odds ratio), comparing the odds of vaccination among subjects testing influenza positive with subjects testing negative, using multivariable logistic regression. Results: Of 1653 participants, 36 of 707 (5%) of those fully vaccinated, 18 of 226 (8%) of those partially vaccinated, and 85 of 720 (12%) of unvaccinated children tested positive for influenza. Of those vaccinated, almost 90% were documented to have received inactivated vaccine. The majority (81%) of influenza cases were in children ≤ 8 years of age. Of the 139 influenza-positive cases, 42% were A(H1N1)pdm09, 42% were B viruses, and 14% were A(H3N2). Overall, adjusted VE for fully vaccinated children was 56% (95% confidence interval [CI], 34%–71%) against any influenza-associated hospitalization, 68% (95% CI, 36%–84%) for A(H1N1)pdm09, and 44% (95% CI, –1% to 69%) for B viruses. Conclusions: These findings demonstrate the importance of annual influenza vaccination in prevention of severe influenza disease and of reducing the number of children who remain unvaccinated or partially vaccinated against influenza. Abstract : In a US surveillance network from 2015 to 2016, full influenza vaccination led to a 56% reduction in the likelihood of children being hospitalized with laboratory-confirmed influenza, highlighting the benefit of influenza vaccination in preventing severe outcomes in fully vaccinated children.